2008
DOI: 10.1080/00036840600994153
|View full text |Cite
|
Sign up to set email alerts
|

Stability of money demand function revisited in China

Abstract: As China's economic reforms have undergone significant structural changes after 1979, it has been rather difficult to formulate a stable money demand function over the period following that year. While previous literature on the long-run relationship of money demand in China shows the existence of stable money demand, this article revisits the stability of the China money demand function over the period after 1979. To employ the unit root tests and the cointegration tests with structural break, the empirical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…The impact of the coefficients changes over the period, with an obvious overall transition between 1993 and 1997. Lee and Chien (2008) who estimated a standard demand for money detected a structural change in 1993. Our location parameter is therefore consistent with their finding although we show that the reform process lasted four years until 1997.…”
Section: Results Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of the coefficients changes over the period, with an obvious overall transition between 1993 and 1997. Lee and Chien (2008) who estimated a standard demand for money detected a structural change in 1993. Our location parameter is therefore consistent with their finding although we show that the reform process lasted four years until 1997.…”
Section: Results Inmentioning
confidence: 99%
“…Only three papers have investigated non-linear, i.e., non-stable relationships, and then only with limited regard to institutional details. Lee and Chien (2008) tested the presence of structural changes and identified one major structural breakpoint in 1993. The drawback is that China is likely to have followed a smooth economic transition process while their model includes only two regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have focused on the cointegration among the variables of money demand function and stability. Employing cointegration techniques, these studies find that the M2 monetary aggregate is cointegrated with income and certain other determinants of money demand, such as price level, interest rate, and economic activity (Baharumshah, Mohd, and Masih 2009;Bahmani-Oskooee and Wang 2007;Hafer and Kutan 1994;Huang 1994;Huang 2000;Lee and Chien 2008;Qin 1994).…”
Section: Economic and Monetary Uncertainty And The Demand For Money Imentioning
confidence: 99%
“…Thus, in order to capture the shocks or volatilities, Atta-Mensah (2004) recommended incorporating economic uncertainty in the estimation of the money demand model. Furthermore, Lee and Chien (2008) analysed the case in China and found that structural breaks in 1980 and 1993 were mainly caused by the economic and financial crisis. Whilst some researchers have focused on the basic model, few studies have attempted to explore the uncertainty model in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%